1997
DOI: 10.1007/s004140050086
|View full text |Cite
|
Sign up to set email alerts
|

Detection of triazolam in skeletal remains buried for 4 years

Abstract: Analyses of the hypnotic triazolam from the remains of two human skeletons buried underground for 4 years were made for purposes of confirmation. The bone marrow and mummified muscle were digested with 2 M sodium hydroxide, efficiently extracted using a 3-step solvent extraction procedure, and selectively analyzed by gas chromatography/mass spectrometry with the negative ion chemical ionization mode. Estazolam was the internal standard used. Triazolam was detected in all the samples; the concentrations were 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 12 publications
1
12
0
1
Order By: Relevance
“…In a third case, triazolam was detected in two BM samples and in one decomposed muscular fragment from two victims found buried, pointing to antemortem administration [67]. These analytical data were in agreement with statements by the suspects, who confessed they had administered triazolam to sedate the victims before burying them alive.…”
Section: Case Reportssupporting
confidence: 81%
See 1 more Smart Citation
“…In a third case, triazolam was detected in two BM samples and in one decomposed muscular fragment from two victims found buried, pointing to antemortem administration [67]. These analytical data were in agreement with statements by the suspects, who confessed they had administered triazolam to sedate the victims before burying them alive.…”
Section: Case Reportssupporting
confidence: 81%
“…In at least six case reports [55,57,[65][66][67][68], toxicological findings were restricted to skeletal tissue analysis. They concerned corpses discovered in skeleton state, 7 months to 5 years after their disappearance.…”
Section: Case Reportsmentioning
confidence: 99%
“…www Moreover, it is encased in bone thus protecting it from possible contamination [9] or degradation. Several drugs including amitriptyline [8], metamphetamine and amphetamine [10], triazolam [11] and bromisovalum [12] have been detected and quantified in human bone marrow. Two conditions are required to ensure a diagnosis of fatal drug intoxication on bone marrow samples.…”
Section: Introductionmentioning
confidence: 99%
“…Midazolam and subnanogram concentrations of triazolam have been reported in bone marrow from individual cases or laboratory studies. 10,11 In the current study, diazepam was the most commonly detected benzodiazepine, and all bone specimens were positive for parent and metabolite. Benzodiazepines, antidepressants, and antipsychotics were reported in a study of 36 cases by McIntyre et al 3 These investigators also reported diazepam as the most common finding.…”
Section: Discussionmentioning
confidence: 51%